Legal Protection of Company Data and Confidential Documents with Confidentiality Clauses in Employment Agreements and Code of Conduct (Case Study of PT Metindo Perkasa Decision Number 459/Pdt/2019/Pt.Bdg) - Felicia Martheo; Ariawan Gunadi (UNES Law Review, 2023)
Protection of company secrets is an important part of ensuring healthy business and business activities. To ensure development activities with fair economic principles, the Indonesian state also strives to protect every business actor who can innovatively create systems and business activities that are mutually beneficial. However, the problem is that monopolistic actions and unhealthy competition often occur and end up with the teacher being one of the parties in a collaboration. For this reason, in order to protect every party in business activities, especially company activities, the state has legal provisions that regulate company secrets. This research aims to find out about legal protection for confidential company data and documents in Indonesia, as well as recognizing the role of work agreements and codes of conduct in the protection of confidential company data and documents. The research method used is descriptive analysis using a statutory approach, a case approach and a conceptual approach. The results of this research indicate that legal protection regarding confidential company documents and data is carried out based on Law no. 8 of 1997 concerning Company Documents and Law no. 30 of 20000 Concerning Trade Secrets, Meanwhile, the role of agreements and codes of conduct is very important in ensuring a healthy relationship between the workforce and the company, and is regulated in Law no. 13 of 2003 concerning Employment.